2013
DOI: 10.1105/tpc.113.118364
|View full text |Cite
|
Sign up to set email alerts
|

The Cold Signaling Attenuator HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENE1 Activates FLOWERING LOCUS C Transcription via Chromatin Remodeling under Short-Term Cold Stress in Arabidopsis    

Abstract: Exposure to short-term cold stress delays flowering by activating the floral repressor FLOWERING LOCUS C (FLC) in Arabidopsis thaliana. The cold signaling attenuator HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENE1 (HOS1) negatively regulates cold responses. Notably, HOS1-deficient mutants exhibit early flowering, and FLC expression is suppressed in the mutants. However, it remains unknown how HOS1 regulates FLC expression. Here, we show that HOS1 induces FLC expression by antagonizing the actions of FVE and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 52 publications
3
109
0
1
Order By: Relevance
“…On the other hand, the double mutant hos1-3 co-10 and the triple mutant hos1-3 co-10 phyB-9 showed that hos1 mutation is still able to accelerate co late flowering phenotype in all combinations tested ( Figures 1D and 1E), indicating that HOS1 has an additional role in flowering time control besides regulating CO. This is consistent with previous data demonstrating that HOS1 is required to maintain high expression levels of the floral repressor FLC (Lee et al, 2001;Lazaro et al, 2012;Jung et al, 2013). We analyzed FLC transcript levels in the single, double, and triple mutant plants and observed that the hos1 mutation consistently reduces FLC expression in every combination analyzed compared with the wild type (Supplemental Figure 1).…”
Section: Hos1 and Phyb Regulate Flowering Time Additivelysupporting
confidence: 77%
See 2 more Smart Citations
“…On the other hand, the double mutant hos1-3 co-10 and the triple mutant hos1-3 co-10 phyB-9 showed that hos1 mutation is still able to accelerate co late flowering phenotype in all combinations tested ( Figures 1D and 1E), indicating that HOS1 has an additional role in flowering time control besides regulating CO. This is consistent with previous data demonstrating that HOS1 is required to maintain high expression levels of the floral repressor FLC (Lee et al, 2001;Lazaro et al, 2012;Jung et al, 2013). We analyzed FLC transcript levels in the single, double, and triple mutant plants and observed that the hos1 mutation consistently reduces FLC expression in every combination analyzed compared with the wild type (Supplemental Figure 1).…”
Section: Hos1 and Phyb Regulate Flowering Time Additivelysupporting
confidence: 77%
“…FLC also plays a role in flowering time control under short-term cold stress, conditions in which flowering is delayed (Seo et al, 2009). The effects of intermittent cold treatments on FLC expression and flowering time are strongly diminished in hos1 mutants (Seo et al, 2009;Jung et al, 2013), indicating that the activation of the FLC gene by cold stress is mediated by HOS1 (Jung et al, 2014). Recently, it has been shown that HOS1 binds to FLC chromatin and that this binding is significantly induced by cold stress (Jung et al, 2013).…”
Section: The Hos1 Mutation Does Not Further Upregulate Ft Expression mentioning
confidence: 99%
See 1 more Smart Citation
“…FLC (FLOWERING LOCUS C) is a floral repressor that integrates vernalization responses (Sheldon et al 2000) and in perennial trees an FLC-like gene has also been highlighted as a candidate for bud dormancy regulation (Porto et al 2015). FLC regulation is basically performed by chromatin remodelling since FLC expression is epigenetically regulated (Shindo et al 2006;Jung et al 2013;Crevillén et al 2014). Taking into account that FLC has a role in xylem differentiation (Sibout et al 2008), it can be surmised that FLC also has a function in phellem development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FVE is also implicated in the photoperiod flowering pathway and is postulated to bind chromatin as a large protein complex of ∼1.0 MDa (54,55). Thus, it is likely that these versatile functions of FVE in environment-controlled flowering are achieved through specific interactions with distinct partners like HOS1 and CUL4-DDB1 (54,56). Collectively, our findings suggest that PTM functions not only as a messenger between chloroplast and nucleus, but also as a multifaceted adaptor to recruit specific partners to trigger diverse transcriptional reprogramming events.…”
Section: Discussionmentioning
confidence: 99%